Biomechanical comparison of semi-rigid pediatric locking nail versus titanium elastic nails in a femur fracture model. (February 2015) - Flinck, Marianne; von Heideken, Johan; Janarv, Per-Mats; Wåtz, Veronica; Riad, Jacques
Background: The treatment for length-unstable diaphyseal femur fractures among school-age children is commonly intramedullary elastic nails, with or without end caps. Another possible treatment is the semi-rigid pediatric locking nail (PLN). The purpose of this biomechanical study was to assess the stability of a length-unstable oblique midshaft fracture in a synthetic femur model stabilized with different combinations of intramedullary elastic nails and with a PLN. Methods: Twenty-four femur models with an intramedullary canal diameter of 10.0 mm were used. Three groups with various combinations of titanium elastic nails (TEN) with end caps and one group with a PLN were tested. An oblique midshaft fracture was created, and the models underwent compression, rotation, flexion/extension, and a varus/valgus test, with 50 and 100 % of the forces generated during walking in corresponding planes. Results: We present the results [median (range)] from 100 % loading during walking. In axial compression, the PLN was less shortened than the combination with two 4.0-mm TEN [by 4.4 (3.4–5.4) mm vs. 5.2 (4.8–6.6) mm, respectively; p = 0.030]. No difference was found in shortening between the PLN and the four 3.0-mm TEN [by 7.0 (3.3–8.4) mm; p = 0.065]. The two 3.0-mm TEN did not withstand the maximum shortening of 10.0 mm. In external rotation, the PLN rotated 12.0° (7.0–16.4°) while the TEN models displaced more than the maximum of 20.0°. No model withstood a maximal rotation of 20.0° internal rotation. In the four-point bending test, in the coronal and the sagittal plane, all combinations except the two 3.0-mm TEN in extension withstood the maximum angulation of 20.0°. Conclusions: PLN provides the greatest stability in all planes compared to TEN models with end caps, even though the difference from the two 4.0-mm or four 3.0-mm TEN models was small.